(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Salvadora oleoids (Family: Salvadoraceae) is being used in the traditional medicine for the treatment of severe bronchitis and asthma. So, the study aims to evaluate anti-asthmatic activity of S. oleoids leaves. Leaves are reported to contain flavonoids, saponins, steroids, alkaloids, and tannins, known to possess similar effects. Flavonoids have been shown to smooth muscle relaxant, bronchodilator, antioxidant, and anti-inflammatory activity. The flavonoids are also reported to inhibit mast cell degranulation. Saponins are reported to mast cell stabilizing, anti-allergic, anti-inflammatory and antihistaminic activity. Tannins are reported to inhibit cyclooxygenase (COX) enzyme, decrease vascular permeability and antioxidant activity. Steroids are reported to an extraordinarily strong anti-inflammatory activity by inhibiting cytokine release IL-1, 2 and 6. The present investigation was undertaken to evaluate the anti-asthmatic activity of ethanolic extract of S. oleoids leaves in experimental animals. Asthma is a chronic inflammatory disorder of the airways. Limitations of currently available therapies and associated side effects have created an urge to search new and better treatment options. Thus, present study was designed to evaluate anti-asthmatic activity of S. oleoids leaves. Ethanolic extract of S. oleoides was prepared and used in the dose of 200 mg/kg (p.o.). Various in-vivo models like histamine induced bronchoconstriction in guinea pigs and milk induced leukocytosis in mice were used for evaluating anti-asthmatic activity of the drugs. Ethanolic extract of S. oleoides showed a significant broncho-dilatory, anti-histaminic and anti-inflammatory activity. Thus, ethanolic extract of S. oleoides have significant anti-asthmatic activity. Thus, ethanolic extract of S. oleoides leaves have proved to be an effective drug in prevention of asthma.